Design and Analysis of an Integrated IoT Electronic Menu Based on The MERN (MongoDB, Express.js, React.js, and Node.js) Stack Website - Syaipuddin Muda Pane; Tulus Ikhsan Nasution (Journal of Technomaterial Physics, 2025)
Restaurants often rely on traditional order-taking processes that are prone to delays, miscommunication, and human error. Earlier IoT-based electronic menus already introduced better order handling, but are limited by unidirectional communication and the scalability constraints of PHP + MySQL architectures. This research investigated the design and analysis of an MERN (MongoDB, Express.js, React.js, and Node.js) stack–based electronic menu, integrated with an Arduino Mega 2560 and ESP8266 module, to enable two-way communication between the client and server. The device was tested under varying Wi-Fi signal conditions, taking into account environmental factors such as distance, humidity, and obstacles. Results showed that Wi-Fi signal strength decreases linearly with distance and is attenuated by 6-7 dBm when passing through a concrete barrier, while high humidity (up to 95%) results in an additional 11-12 dBm reduction. Web application testing demonstrated the reliable data transmission of the MERN stack, which shows a striking difference compared to PHP + MySQL, outperforming it in scalability and processing speed. These results showed the advantages of MERN in supporting an interactive, scalable, and responsive electronic menu. Although measurements were based on averaged trials without complete statistical analysis, a promising approach was demonstrated in improving efficiency and reliability in restaurant environments.